2014
DOI: 10.1093/infdis/jiu326
|View full text |Cite
|
Sign up to set email alerts
|

High Nasopharyngeal Pneumococcal Density, Increased by Viral Coinfection, Is Associated With Invasive Pneumococcal Pneumonia

Abstract: Respiratory virus infection was associated with elevated colonization density and, in turn, invasive pneumococcal pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
162
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 46 publications
11
162
4
2
Order By: Relevance
“…The synergistic effect produced by bacterial and viral co-infection resulting in more severe pneumonia has been described. [17] The severity of AVP as measured by hypoxia and need for ICU admission was associated with both development of PLD and death. This finding is consistent with previous studies looking at outcomes following adenoviral infections.…”
Section: Discussionmentioning
confidence: 96%
“…The synergistic effect produced by bacterial and viral co-infection resulting in more severe pneumonia has been described. [17] The severity of AVP as measured by hypoxia and need for ICU admission was associated with both development of PLD and death. This finding is consistent with previous studies looking at outcomes following adenoviral infections.…”
Section: Discussionmentioning
confidence: 96%
“…A Dutch study reported bacterial isolates in 3.7% blood cultures from ventilated RSV-infected patients, half the rate observed in our study 20 . Given that RSV causes functional changes in respiratory epithelial cells facilitating adherence and invasion of bacteria 21 , excess invasive disease may associate with higher nasopharyngeal carriage rates in infants from developing countries 22,23 . Even then, since between 0.8 to 17.4% bacterial pneumonia yield positive blood cultures 24 , we may be underestimating bacterial burden in RSV mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pneumococcal conjugate vaccine, this is particularly important since both pneumococcal infection and carriage rates are significantly correlated with the severity of the influenza season [10] which fluctuates from year to year. In addition, some pneumococcal serotypes present in epidemic waves that may last several months to a few years [11,12].…”
Section: Discussionmentioning
confidence: 99%